Physico-Chemical and Textural Changes in Elephant Foot Yam (Amorphophallus paeoniifolius) Tubers Infested by the Mealy Bug, Rhizoecus Amorphophalli Betrem during Storage - R S, Sreerag; C A, Jayaprakas; M S, Sajeev (Journal of Postharvest Technology, 2014)
Elephant foot yam, Amorphophallus paeoniifolius is an edible aroid cultivated in the tropical countries. Corm or tuber is the storage organ and is used as seed material or as a vegetable after cooking. Owing to the indisputable palatability, cooking quality, medical utility and therapeutic values of its tubers, this has been dubbed as “King of tubers”. Infestation by the mealy bug, Rhizoecus amorphophalli is a serious problem during its long term storage. This study aims at analysing the physicochemical and textural changes in the mealy bug infested tubers of elephant foot yam. For the study, infested and uninfested tubers were stored for 4 months at ambient conditions and data on the physico-chemical and textural changes were evaluated at monthly interval. The moisture content showed a regular decreasing trend in both uninfested and infested tubers registering higher loss for infested set throughout the storage period. Starch and sugar content decreased with storage period whereas fibre and ash content increased. Functional properties of flours from the uninfested tubers were low compared to the infested tubers and these parameters slightly increased with storage period. Texture profile analysis showed that the firmness of the infested tubers were more than that of the uninfested tubers in their native form.